Upaya Meningkatkan Motivasi Belajar Melalui Kegiatan Ice Breaking Dalam Mata Pelajaran Pendidikan Agama Islam Pada Siswa Kelas III di SD Negeri 2 Gemeksekti Kabupaten Kebumen - Lestari, Wahyu Tri; Munawaroh, Laelatul (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2022)
Students often experience boredom during the teaching and learning process. The success of the learning process cannot be separated from the teacher's ability to implement learning models that focus on increasing the level of student involvement effectively in the learning process. Therefore teachers need to learn the ice breaking method. Ice breaking is a strategy used to warm the atmosphere to create conditions that are more conducive to learning activities. This research aims to investigate the benefits of using the ice breaker learning model for students. The first benefit that can be obtained is creating a conducive atmosphere. The second benefit of ice breaking is increasing familiarity between students. By using ice breaking, students can interact more intimately and get to know each other. This can help build better relationships between students in the classroom. Lastly, ice breaking can also train students' concentration. This research uses action research methods with research subjects consisting of grade 3 students at SD Negeri 2 Gemeksekti. Data was collected from interviews, observation and documentation. Based on the research results of students from cycle I to cycle II, their scores increased. And the results of observations from cycles II to III showed that students' scores increased in understanding the material and focus on learning.